IDENTIFIKASI HAMBATAN GURU DALAM IMPLEMENTASI KURIKULUM ADAPTIF BAGI SISWA AUTIS DI SD INPRES BIRA 2 - Alfi Rachma, Zulvhiqa; Pahira, Hera; Aprianti; Wulandani, Nur; Sulasminah, Dwiyatmi (STKIP Subang, 2026)
This research was driven by the visible discrepancy between inclusive curriculum policies and the actual teaching practices for children with special needs in public elementary schools. The study aimed to identify the implementation of differentiated content, process, and product principles while evaluating how teachers adapted their strategies amidst a lack of formal administrative tools. A descriptive qualitative approach was employed, utilizing in-depth interviews and classroom observations to capture the naturalistic interactions between teachers and students. The findings reveal that teachers perform a “differentiated adaptive” model, relying on pedagogical intuition to compensate for the absence of Individualized Education Programs and specialized special education teachers. While product differentiation effectively flourishes through modified assignments, the learning process remains largely teacher-centered, and student progress documentation lacks a systematic written track. This study concludes that the success of inclusive education in resource-limited settings depends heavily on the pedagogical courage of teachers to implement contextual and independent instructional improvisations.